سوسيولوجيا التنمية المحلية في الجزائر - نعمي نادية; خريبش عبدالقادر (University of Eloued جامعة الوادي, 2024)
ملخص: تهدف هذه الدراسة إلى تسليط الضوء على التحول التكنولوجي واسهامه في تعزيز التنمية المحلية، وهذا باعتبار أن التكنولوجيا الركيزة الأساسية الأهم في التنمية والتي تستعمل كوسيلة للتعجيل بالتقدم الصناعي وبالتالي الرفاه الإجتماعي. فهي تلعب دورا هاما في تطوير الممارسات المحلية التي لا تتناقض مع الجديد وتتماشى مع الواقع الخصوصي لكل مجتمع، لهذا سعت الجزائر في بداية السبعينات من القرن الماضي الإعتماد على الصناعات المصنعة الثقيلة وبكفاءات جزائرية وهذا من خلال استراد التكنولوجيا الصناعية لتحقيق التنمية المحلية ورفاه الاجتماعي لساكنة. وخلصت هذه الدراسة إلى نتيجة مفادها أن عملية التحول التكنولوجي في الجزائر ضرورة حتمية اليوم في ظل التحولات العالمية ،فهي عملية شاملة ومترابطة يجب أن تعتبر ثقافة من أجل النهوض بالتنمية. Abstract: The aim of this study is to highlight the technological transformation and its contribution to enhancing local development, considering that technology is the most important cornerstone in development, and is used as a means to accelerate industrial progress and thus social welfare. It plays an important role in developing local practices that do not contradict the new and are in line with the specific reality of each society. Therefore, Algeria sought in the early 1970s to rely on heavy manufacturing industries with Algerian competencies through the importation of industrial technology to achieve local development and social welfare for its population. This study concludes that the process of technological transformation in Algeria is an inevitable necessity today in the face of global transformations. It is a comprehensive and interconnected process that should be considered a culture in order to promote development
مدخل التغير التكنولوجي
Keywords: التكنولوجيا; التحول التكنولوجي; التنمية المحلية; التنمية المستدامة; technology; technological transformation; local development; sustainable development